The Paradoxical Role of Cellular Senescence in Cancer - Yang, Jing; Liu, Mengmeng; Hong, Dongchun; Zeng, Musheng; Zhang, Xing (Frontiers in Cell and Developmental Biology, 2021)
Cellular senescence occurs in proliferating cells as a consequence of various triggers including telomere shortening, DNA damage, and inappropriate expression of oncogenes. The senescent state is accompanied by failure to reenter the cell cycle under mitotic stimulation, resistance to cell death and enhanced secretory phenotype. A growing number of studies have convincingly demonstrated a paradoxical role for spontaneous senescence and therapy-induced senescence, that senescence may involve both cancer prevention and cancer aggressiveness. Cellular senescence was initially described as a physiological suppressor mechanism of tumor cells, because cancer development requires cell proliferation. However, there is growing evidence that senescent cells may contribute to oncogenesis, partly in a senescence-associated secretory phenotype (SASP)-dependent manner. On the one hand, SASP prevents cell division and promotes immune clearance of damaged cells, thereby avoiding tumor development. On the other hand, SASP contributes to tumor progression and relapse through creating an immunosuppressive environment. In this review, we performed a review to summarize both bright and dark sides of senescence in cancer, and the strategies to handle senescence in cancer therapy were also discussed.